Copper foils used as support for catalytic monoliths. Superficial nano/microstructures obtained for two treatments - Morales, Maria Roxana (2013)
Copper metallic monoliths were thermally and chemical treated. Copper oxides with different nano/microstructures were obtained applying different variables in both treatments. They showed to be stable and suitable to act as support of the Mn9Cu1 catalyst bulk or as an active catalytic phase. Two monoliths representing each treatment were evaluated in the combustion of toluene. Both showed a good performance.